2009
DOI: 10.2478/s11536-009-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Lithuanian population: the impact of country residence and socio-economic status

Abstract: AbstractQuality of life (QoL) and individual perception of health has become a subject of great interest in Lithuania. The relationships between country residence, socio-economic status (SES), and QoL have not been well characterized among the Lithuanian urban and rural populations. The aim of the study was to assess the influence of country residence and SES on QoL in Lithuanian urban and rural population adjusting for the influence of other known determinants of QoL. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
1
2
0
1
Order By: Relevance
“…Similarly, in the study by Wang et al [ 33 ], the respondents' quality of life was significantly and positively associated with the level of annual income. An increase in the values of health-related quality of life with the improvement of material situation, mainly the income level, was also reported by Nayir et al [ 16 ], Kulik et al [ 51 ], Rėklaitienė et al [ 52 ], Kooi-Yau Chean et al [ 53 ], Povey et al [ 54 ], Han et al [ 41 ], Huang et al [ 55 ] and Song et al [ 38 ]. The highest quality of life assessment in people with the highest income was found by Rezaei et al [ 17 ], while the lowest quality of life assessment in people with the lowest income by Zhang et al [ 56 ].…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, in the study by Wang et al [ 33 ], the respondents' quality of life was significantly and positively associated with the level of annual income. An increase in the values of health-related quality of life with the improvement of material situation, mainly the income level, was also reported by Nayir et al [ 16 ], Kulik et al [ 51 ], Rėklaitienė et al [ 52 ], Kooi-Yau Chean et al [ 53 ], Povey et al [ 54 ], Han et al [ 41 ], Huang et al [ 55 ] and Song et al [ 38 ]. The highest quality of life assessment in people with the highest income was found by Rezaei et al [ 17 ], while the lowest quality of life assessment in people with the lowest income by Zhang et al [ 56 ].…”
Section: Discussionsupporting
confidence: 55%
“…The multiple regression analysis though did not confirm such a high impact since only two scales, general health and mental health was statistically influenced in the rural population. It is of interest that some studies demonstrated that the rural population in America reports better satisfaction with their health status (Cleary and Howell 2006;Philip et al 2002) and that inhabitants of village communities are more satisfied with their life situation which improves their health status perception (Reklaitiene et al 2009). The residence-specific analysis showed that primary education was associated with impaired HRQoL in both rural and urban areas, whereas the impact of income was more profound for the rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…Major efforts in different areas of knowledge are being made to attend to this population's growing demands. In the health sciences, many studies have been developed to investigate their quality of life (QOL) (Kato et al, ; Walker, ; Rėklaitienė et al, ).…”
mentioning
confidence: 99%